A prospective comparative study between biodegradable temporizing matrix (BTM) and Matriderm in the reconstruction of lower lip and limb contractures. - Sumesh Ramesh Doiphode; Dr. Subhash Kumar; Setu Bandhu Tiwary (Student's Journal of Health Research Africa, 2025)
Background: Reconstruction of post-burn and post-traumatic contractures, especially in the lower lip and limbs, requires an effective dermal substitute to restore both function and aesthetics. Biodegradable Temporizing Matrix (BTM) and MatriDerm® are two commonly used options with distinct properties. Aim: To compare the clinical outcomes of BTM and MatriDerm® in the surgical reconstruction of lower lip and limb contractures. Materials and methods: A prospective comparative study was conducted over 3 years at Patna Medical College and Hospital, involving 50 patients. Patients were randomly assigned to two groups: Group A (BTM, n = 25) and Group B (MatriDerm®, n = 25). Outcome measures included graft take, healing time, infection rate, aesthetic appearance, functional recovery, and patient satisfaction. Results: The study population comprised 27 males (54%) and 23 females (46%), aged 10–60 years (mean 32.4 ± 9.8 years). BTM demonstrated superior graft take (A1: 94%, A2: 91%) compared to MatriDerm® (B1: 88%, B2: 83%). MatriDerm® showed faster healing (B1: 16 days, B2: 18 days), but at the cost of higher infection rates (B1: 11%, B2: 22%). BTM groups had better aesthetic scores (A1: 8.8, A2: 8.3), functional recovery (A1: 91%, A2: 87%), and patient satisfaction (A1: 9.0, A2: 8.5). Lip reconstructions generally had better outcomes than hand reconstructions. Conclusion: BTM is more effective than MatriDerm® in achieving durable reconstruction with fewer complications. Individual patient assessment and further large-scale studies are recommended. Recommendation: MatriDerm® can be saved for smaller or less contaminated wounds, whereas BTM is advised for complex or mobile areas. It is necessary to do more extensive, multicentric research.